Risk Factors for Gestational Diabetes Mellitus among Pregnant Women Attending Antenatal Clinic in Kisumu City, Western Kenya - Ottaro, Anita Amukhuma; Ayodo, George; Amolo, Asito S. (Research Square, 2023)
Background: Globally there is a rapid increase in the prevalence of Gestational diabetes mellitus (GDM) associated with adverse maternal and neonatal outcomes. However, screening for GDM is not part of the standard routine antenatal (ANC) services in Kenya. There is a paucity of data on the factors associated with and predictors of GDM. Therefore, this study sought to determine factors associated with and predictors of GDM among pregnant women in western Kenya. Methods: A case-control study was conducted from September 2021-October 2022. Using a validated questionnaire, data were obtained from 210 randomly sampled pregnant women attending antenatal clinic at Jaramogi Oginga Odinga Teaching and Referral Hospital (JOOTRH) in Kisumu city, western Kenya. Screening and diagnosis for Gestational Diabetes mellitus was performed using the 2013 World Health Organization (WHO) criteria. Both descriptive and inferential statistical analysis were done in SPSS V.23 using Chi-square (χ2) test to test for associations and Binary logistic regression analysis to determine predictors of GDM. Results: Among the 105 GDM cases, majority were in 30-34 years age group (51%), overweight with a BMI of 25-29.9 kg/m2 (56%), had history of hypertension (53%), had hypertensive relatives (64%), had history of glycosuria (64%), were multiparous (69%), had history of cesarean delivery (61%), had history of macrosomic delivery (63%) and had history of neonatal intensive care unit (NICU) admission (53%). Multivariate analysis revealed that living in peri-urban area (adjusted OR [aOR] 3.30, 95%CI: 1.04-11.3,p=0.048), having a diabetic relative (aOR 8.09, 95%CI: 1.44- 73.0, p=0.031), being on iron-folic acid supplementation (IFAS) (aOR 13.0, 95%CI: 4.37-47.8, <0.001), having history of neonatal intensive care unit admission (NICU) (aOR 13.9, 95%CI: 3.45-70.5, p<0.001) and history of caesarean delivery (aOR 5.02,95%CI: 1.42-19.5, p=0.015) significantly increased the odds of having GDM. Conclusion: The predictors of GDM include having a diabetic relative, history of cesarean section, NICU admission and being on IFAS. There is need to incorporate GDM screening in the standard ANC services for optimal pregnancy outcomes. Multicenter studies looking at the long term effects of IFAS should be carried out to inform evidence based nutrition interventions during pregnancy.
Keywords: Gestational Diabetes Mellitus; Cesarean Section; Macrosomia; Iron and Folic Acid Supplementation (IFAS)